Pengaruh Pakan Kompilasi yang Mengandung Kelor dan Bakteri Asam Laktat (BAL) Terhadap Gambaran Trombosit Ayam Broiler - Foeh, Nancy; Fanmira, Aska; Ndaong, Nemay; Detha, Annytha; Datta, Frans Umbu (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
The aim of this study was to examine the effect of lactic acid bacteria (LAB) and Moringa in the compilation of feed for broiler chickens. This research was conducted from June to November 2021, in the Nekamese chicken coop, Kupang district. The study used a completely randomized design using 4 treatment designs. Chickens are fed approximately 3 kg a day 2 times in the morning and evening, with drinking water given at libitum. The test results showed that for each treatment group, the feed containing Moringa and lactic acid bacteria isolates from palm sap on broiler chickens did not show a significant effect. However, if viewed descriptively, it shows the difference from the average difference in treatment. The average platelet value in the treatment group was higher than the control group. Further research is needed with a larger sample size related to Moringa as broiler chicken feed.